(untitled) (Journal of the College of Basic Education, 2023)
Building a scale of distinctive leadership styles for faculty members in colleges and departments of physical education and sports sciences in Baghdad Keywords (building a scale - physical education teachers) masters student Miqdad Qassem Muhammad Sakr Al-Azergawi Research Summary: The importance of the research lies in the researcher’s approach to the concept of leadership styles and studying it in all respects. And it is the first Iraqi study (to the researcher’s knowledge) that deals with this variable in the sports field. As for the research problem, it lies in the absence of a measuring tool that measures this concept among faculty members and disclose it. The research objectives were to build a leadership styles scale for physical education teachers, build a scale of distinctive leadership styles for faculty members in faculties and departments of physical education and sports sciences for the academic year (2021-2022) The descriptive approach was used, and the researcher relied on the measures of building the scale through what the researcher obtained from the description of leadership styles, and his fields were determined by presenting the survey form to a group of experts and specialists, and setting a definition for each field, and it was identified with five fields. The five-point scale was used. And based on the opinion of the experts, (52) items were kept distributed on the five scale areas, and the researcher conducted an exploratory experiment on a sample from outside the basic research sample. Then the scale was applied to the basic experiment sample (construction sample) of (100) teachers who were chosen by the grill method. The researcher used two statistical methods to analyze the paragraphs: the extremist groups method and the internal consistency method. In light of the results that appeared, the paragraphs containing a discriminatory force with a moral significance were accepted. This procedure was applied to all paragraphs, and some paragraphs were deleted because they did not reach the level of significance. Validity was verified using content validity and construction validity, as well as stability was verified by the half-segmentation method and Cronbach’s alpha. The statistical package for social sciences (SPSS) was used to extract the research results: The researcher reached the following conclusions: Scale construction has been reached Building a scale of distinctive leadership styles for faculty members in colleges and departments of physical education and sports sciences in Baghdad 2- Five axes of the leadership styles scale for teachers of physical education and sports sciences were extracted based on the results of the statistical analysis. The scale items amounted to (52) items distributed among the axes as follows: A- The first factor was called the axis (the traditional pattern), and it contained (12) paragraphs. B - The second factor was called the axis (the democratic style) and it contained (10) paragraphs C- The third factor was called the axis (the dictatorial style) and it contained (10) paragraphs D - The fourth factor was called the axis (style of social support) and it contained (10) paragraphs E - The fifth factor was called the axis (positive reinforcement pattern) and it contained (10) paragraphs